FUNCTIONING GRAPHIC ORGANIZER AS ONE OF LITERACY MEDIA - Tarwiyah, Siti (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2015)
Graphic organizer may be used as alternative media in literacyclass. GO stimulates students to think of information through someways. Through the use of GO students’ habbit to copy others’ ideaswill be minimized. Students only need to take the key words repre-senting the digest of the information in a text and think of the re-lationship among the words. Some kinds of graphic organizer maybe used are story map, fi shbone or ishikawa diagram, venn diagram,and KWL table.